Learning Media Application for Basic Digital Courses Using Augmented Reality with the Marker Based Tracking (MBT) Method - Syamsul Buchori Pane; Eva Darnila; Fajriana Fajriana (ITEJ (Information Technology Engineering Journals), 2025)
The rapid development of digital technology opens up opportunities to increase the effectiveness of learning media, one of which is by utilizing Augmented Reality (AR) technology. This study aims to develop an AR-based digital basic course learning media application with the marker-based tracking method. The materials presented include number systems, logic gates, boolean algebra, Karnaugh maps, and flip-flops. The development process is carried out through a waterfall approach which includes literature studies, needs analysis, system design, implementation, and testing. The results of the study show that the developed application is able to display 3D objects interactively and in real-time through features such as rotation, zoom, and audio, so as to improve students' understanding and interest in learning. The application of AR technology has proven to be an innovative and effective medium in conveying abstract concepts in digital learning.